Chitosan/graphene oxide composite film for adsorption of Cu2+ ions - Majid, M. A. H. M. A.; Osman, N. H.; Tamchek, N.; Ramli, M. M.; Sukri, N. A. A.; Mazlan, H. I.; Mazu, N. N.; Idris, A.; Błoch, K.; Gondro, J. (Polska Akademia Nauk, 2022)
Many materials have been studied to detect and remove pollution from the aqueous environment. In this study, chitosan (CH)/graphene oxide (GO) composite film was prepared with the intention of removal of copper ions (Cu2+). The film adsorption capability of Cu2+ was analyzed at different parameters such as contact time, initial concentrations of Cu2+, and CH to GO ratio. The film with a ratio of 1:5 showed the highest adsorption capability, with the film reaching equilibrium at 60 min. The initial concentration data fit well with the Langmuir isotherm model compared to the Freundlich isotherm model, showing that adsorption was the primary mechanism for removal. The maximum adsorption capacity recorded in this work was 39.96 mg/g. Hence, the CH/GO composite film has potential application in the removal of Cu2+ from wastewater.